2019
DOI: 10.15252/embr.201846570
|View full text |Cite
|
Sign up to set email alerts
|

UBTD1 is a mechano‐regulator controlling cancer aggressiveness

Abstract: Ubiquitin domain‐containing protein 1 (UBTD1) is highly evolutionary conserved and has been described to interact with E2 enzymes of the ubiquitin–proteasome system. However, its biological role and the functional significance of this interaction remain largely unknown. Here, we demonstrate that depletion of UBTD1 drastically affects the mechanical properties of epithelial cancer cells via RhoA activation and strongly promotes their aggressiveness. On a stiff matrix, UBTD1 expression is regulated by cell–cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…This critical switch is controlled by EGFR ubiquitination [33,34]. We and others showed by antibody-based and antibody-free methods that UBTD1 is localized in various cell compartments including the plasma membrane, ER and vesicles [14,35]. Therefore, we first speculated that UBTD1 was implicated in EGFR cargoes internalization through ubiquitination of the receptor.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This critical switch is controlled by EGFR ubiquitination [33,34]. We and others showed by antibody-based and antibody-free methods that UBTD1 is localized in various cell compartments including the plasma membrane, ER and vesicles [14,35]. Therefore, we first speculated that UBTD1 was implicated in EGFR cargoes internalization through ubiquitination of the receptor.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, we have shown that UBTD1 controls the degradation of the transcriptional regulator YAP (yesassociated protein) by modulating its ubiquitination [14]. Mechanistically, UBTD1 is a component of the ubiquitination complex that allows the E3 ligase β-TRCP (beta-transducin repeats-containing proteins) to interact with YAP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from actin filament polymerization based protrusive forces, it has been hypothesized that the suppression of myosin contractility has an impact on the directionality of cell movement (Puleo et al, 2019). There is an upregulation of genes/proteins such as Ubiquitin domain−containing protein 1 (UBTD 1) that interact with E2 enzymes of the ubiquitin-proteasome system due to environmental cues, such as stiff matrices (Torrino et al, 2019). Rather unexpected is the fact that suppression of myosin activity had no impact on mechanically guided directed motility.…”
Section: Cytoskeletal Mechanicsmentioning
confidence: 99%